Trypanosoma cruzi invasion is associated with trogocytosis - Mukherjee, Shankar (Microbes Infect, 2014)
Trogocytosis was originally thought to be restricted to the interaction of cells of the immune system and interactions of these cells with cancer cells. Such membrane exchanges are probably a general process in cell biology, and membrane exchange has been demonstrated to occur between non-immune cells within an organism. Herein, we report that membrane and protein exchange, consistent with trogocytosis, between Trypanosoma cruzi (both the Brazil and Tulahuen strains) and the mammalian cells it infects. Transfer of labeled membrane patches was monitored by labeling of either parasites or host cells, i.e. human foreskin fibroblasts and rat myoblasts. Trypomastigotes and amastigotes transferred specific surface glycoproteins to the host cells along with membranes. Exchange of membranes between the parasite and host cells occurred during successful invasion. Extracellular amastigotes did not transfer membrane patches and heat killed trypomastigotes were did not transfer either membranes or proteins to the host cells. Membrane exchange was also found to occur between interacting epimastigotes in cell-free culture and may be important in parasite-parasite interactions as well. Further studies should provide new insights into pathogenesis and provide targets for therapeutic intervention.